Pengaruh Implementasi Pembelajaran Kooperatif Tipe Numbered Head Together (NHT) Terhadap Self Efficacy dan Hasil Belajar Matematika Siswa Sekolah Dasar - Gazali Gazali; I Made Ardana; I Wayan Lasmawan (SENTRI: Jurnal Riset Ilmiah, 2025)
This study aims to determine the differences in the effect of the cooperative learning model Number Heads Together (NHT) on self-efficacy and mathematics learning outcomes of elementary school students. The population of the study consisted of all fourth-grade students at SD Negeri 03 Mamben Lauk, totaling 69 students, with 68 students selected as the sample using simple random sampling. This research employed a quasi-experimental design with a Single Factor Independent Group Design. The results of the first hypothesis test showed an F-value of 6.026 with a significance of 0.017 < 0.05, indicating that H₀ is rejected and H₁ is accepted. This means there is a significant difference in self-efficacy between students who received the NHT cooperative learning model and those who received conventional learning. The second hypothesis test revealed an F-value of 14.538 with a significance of 0.000 < 0.05, suggesting a significant difference in students’ science literacy between those taught using portfolio assessment and those with conventional assessment. The third hypothesis test yielded an F-value of 7.965 with a significance of 0.001 < 0.05, indicating a significant simultaneous difference in both self-efficacy and learning outcomes between students taught using the NHT model and those taught conventionally.